Dentigerous cyst in an uncommon site: A rare entity - K P Bharath; V Revathy; S Poornima; V V Subba Reddy (Wolters Kluwer Medknow Publications, 2011)
Trauma to the deciduous teeth may have severe consequences. Pulp necrosis is the commonly observed sequel in traumatized primary teeth and is one of the possible etiologic factors for the development of dentigerous cyst. Dentigerous cyst is more commonly seen in mandibular third molar and maxillary canine region and is rarely associated with other teeth. This article addresses a case of dentigerous cyst associated with the germ of upper permanent central incisor, an uncommon site of occurrence, which was impacted, dislodged from its natural site of eruption after trauma to the predecessor incisor.